(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрена структура факторов безаварийности прохождения сложных водных маршрутов. Выделено две группы факторов: непрогнозируемые и прогнозируемые. Разработан метод учёта действия каждого фактора и оценивания в баллах в зависимости от вариантов его проявления. Предложена формула расчета фактора безаварийного прохождения водного маршрута и выполнен его расчет применительно водному маршруту III категории сложности. К л ю ч е в ы е с л о в а: туризм; водные маршруты; факторы безаварийности. WHIGHT WATER ROUTES ACCIDENT-FREE PASSAGE FACTORS The goal of the work is the Wight water accidents reduction. The subject of research is Wight water routes accident-free passage factors. The quantitative method of risks estimation is offered. Accident-free passage factors classification has been done. They were divided as predictable and unpredictable. The predictable factors formed hierarchical structure of human organization and passage accident-free factors and technical. The factors itself consist of risk elements. The formula of accident-free passage factor calculation has been evaluated. The advantages of this method are the scientifically objective forecasting risks, simple calculation algorithm and unification risks estimation. But it is necessary to realize that unpredictable factors can reduce Wight water routes safety. For practical approbation the calculation the accident-free passage factor for 3rd level Wight water route was provided. They were correlated with expert estimation and practical results of real route passage. Looking foreword after special adoption this method can be useful for other tourism activities. K e y w o r d s: tourism; white water routes; accident-free factors.